An in-vitro evaluation of direct thrombin inhibitor and factor Xa inhibitor on tissue factor-induced thrombin generation and platelet aggregation: a comparison of dabigatran and rivaroxaban. Issue 8 (December 2016) - Wan, Huaibin; Yang, Yanmin; Zhu, Jun; Wu, Shuang; Zhou, Zhou; Huang, Bi; Wang, Juan; Shao, Xinghui; Zhang, Han
Abstract : Dabigatran and rivaroxaban may simultaneously inhibit coagulation and platelet activation. This study aimed to reveal the in-vitro effects of dabigatran and rivaroxaban on thrombin generation and platelet aggregation (PAg) derived via tissue factor (TF) pathway. Citrated blood was obtained from six healthy adults (26–60 years old) and pretreated with increasing concentrations of dabigatran or rivaroxaban. Plasmatic endogenous thrombin potential (ETP) was measured by the calibrated automated thrombogram method. The whole blood PAg was evaluated via a kinetic counting method. TF produced an ETP of 1904.69 ± 121.42 nmol min and a PAg of 78 ± 5%. Dabigatran and rivaroxaban concentration-dependently reduced ETP with half-maximal inhibitory concentrations of 460.1 ± 1.4 and 678.1 ± 1.4 nmol/l, and inhibited PAg with half-maximal inhibitory concentrations of 119.5 ± 1.5 and 77.5 ± 1.6 nmol, respectively. Dabigatran and rivaroxaban significantly inhibit TF-induced hypercoagulation and platelet activation in vitro in a concentration-dependent manner. Rivaroxaban displays stronger inhibition on thrombin generation and PAg than dabigatran.